المساندة الاجتماعية وعلاقتها بالضغوط النفسية المزمنة دراسة ميدانية على عينة من طلبة كلية التربية بجامعة دمشق - درويش, رمضان; جاموس, ياسر; الذياب, حكمات (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف هذا البحث إلى الكشف عن العلاقة المحتملة، بين المساندة الاجتماعية والضغوط النفسية المزمنة، لدى عينة من طلبـة جامعة دمشق – كلية التربية -حيث بلغ عدد أفراد عينة البحث (200)طالباً وطالبة، كما يحاول هذا البحث معرفة الفروق في أداء أفراد عينة البحث، على أدوات البحث، التي تعزى إلى متغير الجنس، وبعد اختبار الفرضيات تم التوصل إلى النتائج التالية: وجود ارتباط ايجابي دال إحصائيا عند مستوى الدلالة (0.01) بين المساندة الاجتماعية المقدمة من الأسرة والأصدقاء، والضغوط النفسية المزمنة. عدم وجود ارتباط بين دال إحصائيا عند مستوى الدلالة (0.01) الضغوط النفسية، والمساندة الاجتماعية، المقدمة من المجتمع. وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (0.01) بين الذكور، والإناث، بالمساندة الاجتماعية، المقدمة من الأسرة لصالح الإناث. وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (0.01) بين الذكور، والإناث، بالمساندة المقدمة من الأصدقاء لصالح الذكور. عدم وجود فروق ذات دلالة إحصائية، عند مستوى الدلالة (0.01) بين الذكور، والإناث، بالمساندة المقدمة من المجتمع. وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (0.01) بين الذكور، والإناث، في الضغوط النفسية لصالح الإناث. وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (0.01) بين طلاب السنة الأولى، والرابعة، في المساندة الاجتماعية المقدمة من الأسرة لصالح السنة الأولى. عدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (0.01) بين السنة الأولى، والرابعة، في المساندة المقدمة من الأصدقاء. وجود فروق ذات دلالة إحصائية، عند مستوى الدلالة (0.01) في المساندة المقدمة من المجتمع لصالح طلاب السنة الرابعة. وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (0.01) في الضغوط النفسية المزمنة، لصالح السنة الأولى. This research aims to discover the possible relationship between social helping and chronic psychological stress on a sample from Damascus university students – faculty of education -the number of student reach 200.This research also try to know the difference between sample members ‘performance on research tools, which is due to the sex variable After testing assumptions we reach these results: 1- There is a positive significant correlation on (0.01) level between social helping that affords from family and friends, and chronic psychological stress. 2- There is no correlation between psychological stress, and social helping that affords from community. 3- There are significant differences correlation on (0.01) level between males and females in psychological stress on the accounts of females. 4- There are significant statistical differences on (0.01) level between males and females in social helping which affords from family on the accounts of female. 5- There are significant statistical differences on (0.01) level between males and females in social helping that affords from friends on the accounts of male. 6- There is no significant statistical difference on (0.01) level between males and females in social helping that affords from community. 7- There are significant statistical differences on (0.01) level between first grade students and fourth grade in social helping that affords from family on first grade account. 8- There is no significant statistical difference on (0.01) level between first and fourth grade in social helping that affords from friends 9- There are significant statistical differences on (0.01) level in social helping that affords from community on the accounts of fourth grade. 10- There are significant statistical differences on (0.01) level in chronic psychological stress on the accounts of first year.